Effects of Essential Fatty Acids Containing Natural and Commercial Diets on Larvae Rearing of the Green Mud Crab Scylla Paramamosain (Estampador 1949) - Islam, M. L.; Islam, M. S.; Yahya, K.; Hashim, R. (Journal of Scientific Research, 2017)
Effect of essential fatty acids (EFA) on growth and survival of the green mud crab (Scylla paramamosain) larvae was assessed by feeding with natural to commercial diets. The feeding schemes were: larvae reared with Artemia (T1); larvae initially fed with rotifers (up to Z2) and ended (Z3 to megalopa) with Artemia (T2); and larvae fed with rotifers up to Z2 and ended (Z3 to megalopa) with commercial diet (T3). The commercial diet had significantly (p<0.05) higher levels of docosahexaenoic acid (11.23%), ?n-3s (15.90%) and ?n-6s (4.21%); and lacked in eicosapentaenoic acid (2.25%) than rotifer and Artemia. The earliest commencement of megalopa stage within 15 days with significantly (p<0.05) higher larval stage index (LSI) of 5.90±0.17 was achieved from the feeding scheme of T2 than other two feeding schemes. This feeding scheme deposited 17.32±0.19% eicosapentaenoic acid (EPA) and 3.82±0.11% docosahexaenoic acid (DHA); the ?n-3 to ?n-6 ratio of 0.20 and EPA to DHA ratio of 0.22 in megalopa, that stimulated significantly higher (p<0.05) megalopa survival (20.00±6.96%) indicating the superiority over rest feeding schemes. Meanwhile, some deformities and mortalities in Z5 and megalopa stages suggested further studies for optimization of specific fatty acid requirements for late larval stages (Z5 and megalopa).